Adolescências e saúde mental: um diálogo a partir da estratégia do cine debate - Fabi, Rafaela Mancini (Universidade Federal de São Carlos, 2023)
The literature in the field of child and adolescent mental health points to the school context as a potent space for the development of actions promoting the mental health of teenagers, but it also signals a shortage of national papers on this theme, especially concerning the involvement of teenagers in the process of producing knowledge about themselves. Thus, the present research aims to understand and analyze, in collaboration with adolescent students from a public school, elements related to the theme of mental health in adolescence using the “Cine Debate” strategy. A qualitative research was conducted using the creative strategy of “Cine Debate”. Teenagers from a public school in the second cycle of elementary education participated in the study, attending 2 sessions where films were screened, followed by discussions. The participating teenagers also responded to a questionnaire for process evaluation. The discussions and the evaluative process were subjected to Bardin's Thematic Analysis. Three themes emerged from the analysis of the results: "Perspectives on relationships: challenges, obstacles, and importance"; "Feeling in adolescence"; "Cine Debate: how to be a possible strategy." The study contributes to presenting the perspectives of teenagers on this stage of life, on social support, and on possible ways to conduct a debate activity based on the theme of mental health in the school context.
Adolescences and mental health: a dialogue from the cine debate strategy
Keywords: Saúde Mental; Adolescências; Cine-debate; Métodos criativos; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA